Development of directions for optimizing the conditions for the functioning subjects of small and medium businesses in the Republic of Kazakhstan based on the experience of developed countries - Bayandina, G.D.; Bayandin, M.A.; Mashrapov, N.K. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The article reveals the development of directions for optimizing the conditions for the functioning subjects of small and medium businesses in the Republic of Kazakhstan based on the experience of developed countries. The article introduces the study of small and medium businesses development based on the experience of the United States, France, Germany, and Singapore. The world experience is of particular interest in studying the facilitation of state support for small and medium enterprises. The particular attention is focused on the role and significance of the SMEs activities in various countries, namely, the micro and macroeconomic indicators, such as the level of competition and employment, the introduction of new technologies and production efficiency, structural changes in the economy, etc. depend on the efficiency and scale of the SMEs activity. The experience of developed countries indicates that the development and expansion of small and medium-sized enterprises create favorable conditions for economic recovery, a competitive environment is being developed, as well as the sectoral and regional monopoly is being overcome.